2000
DOI: 10.1002/(sici)1099-0690(200002)2000:4<583::aid-ejoc583>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

D2-Symmetric Chiroporphyrins Derived from (1R)-cis-Hemicaronaldehydic Acid: Preparation and Spectral Characterization

Abstract: Esters, N,N‐disubstituted amides, and a N‐acylurea derived from the enantiopure industrial intermediate (1R)‐cis‐hemicaronaldehydic acid (or biocartol) are convenient synthons for the preparation of a series of chiroporphyrins by condensation with pyrrole. These chiral meso‐tetracyclopropylporphyrins are obtained exclusively as the D2‐symmetric α,β,α,β atropisomer, generally in low to moderate yields (2‐20%), and in the urea case in excellent yield (60%). Hydrolysis of the urea substituents affords a chiroporp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The internal NH protons can also be an efficient probe with which to evaluate the macrocycle distortion, as illustrated with chiroporphyrins. [23] Nevertheless, in consideration of the very different influence that the aromatic ring of the strap, because of its apical position, may have on the NH internal protons, we decided not to take these into account. Obviously, the aromatic cycle can shield these two protons if in a parallel orientation, as in porphyrins 5, but should have the opposite effect if perpendicular to the porphyrin as in 6.…”
Section: Resultsmentioning
confidence: 90%
“…The internal NH protons can also be an efficient probe with which to evaluate the macrocycle distortion, as illustrated with chiroporphyrins. [23] Nevertheless, in consideration of the very different influence that the aromatic ring of the strap, because of its apical position, may have on the NH internal protons, we decided not to take these into account. Obviously, the aromatic cycle can shield these two protons if in a parallel orientation, as in porphyrins 5, but should have the opposite effect if perpendicular to the porphyrin as in 6.…”
Section: Resultsmentioning
confidence: 90%
“…2TPyP, and indeed 1, have the additional property that the free rotation of the pyridyl groups in solution at room temperature can lead to four major possible conformational isomers in the solid-state (Scheme 1b). In the reported structure, 2TPyP adopts the abab [25] conformation [21]. Clearly, detailed structural information about 1 is important for a better understanding of the factors that determine these differences.…”
Section: Introductionmentioning
confidence: 99%
“…[165] A following paper, however, reported that only the αβαβ-atropisomer was formed for the porphyrin esters MnCl-TCarRP. [166] This work also suggests that the degree of distortion of the porphyrin macrocycle in the free base porphyrin can be related to the chemical shift of the NH protons in the 1 H NMR spectra. Later the correlation between the distortion of the free base porphyrin (represented by δ NH ) and the ee of the epoxidation reaction catalyzed by the corresponding Mn-complex was highlighted.…”
Section: Epoxidation Reactionsmentioning
confidence: 74%
“…reported the effect of varying the ester group in MnCl‐ TCarRP ( 90 ) on the catalytic properties, and found that increasing the steric crowding led to an increase in the ee for epoxidation of dihydronapthalene; however, this work did not discuss the different atropisomers [165] . A following paper, however, reported that only the αβαβ ‐atropisomer was formed for the porphyrin esters MnCl‐ TCarRP [166] . This work also suggests that the degree of distortion of the porphyrin macrocycle in the free base porphyrin can be related to the chemical shift of the NH protons in the 1 H NMR spectra.…”
Section: Applications In Catalysismentioning
confidence: 93%